1998
DOI: 10.1093/chromsci/36.8.388
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Liquid Chromatography on Calixarene-Bonded Silica Gels. III. Separations of cis/trans Isomers of Proline-Containing Peptides

Abstract: The liquid chromatographic behavior of p-tert-butylcalix[n]arene (n = 4,5,6, and 8) for the separation of cis/trans peptide bond isomers of proline-containing peptides is studied to demonstrate the chromatographic selectivity of calixarene stationary phases. The results are compared with the elution patterns obtained on RP18 and β-cyclodextrin, as well as on a monomeric p-tert-butylphenoxyacetic acid. The chromatographic data are established by rechromatography and 1 H-NMR spectroscopy. The results support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…His group estimated isomerization rate constants and the activation barrier of some proline-containing dipeptides by computer-supported Damköhler analysis, a method that is commonly used in chemical engineering. Krauss et al [12][13][14][15] and Gesquiere et al [16] also found isomerization of prolinecontaining peptides taking place on different stationary phases in HPLC and Thomas et al [17], Wüthrich et al [18], and Moroder et al [19] in NMR studies.…”
Section: Enalaprilat (1-[n-[(s)-1-carboxy-3-phenylpropyl]-l-alanyl]-mentioning
confidence: 94%
“…His group estimated isomerization rate constants and the activation barrier of some proline-containing dipeptides by computer-supported Damköhler analysis, a method that is commonly used in chemical engineering. Krauss et al [12][13][14][15] and Gesquiere et al [16] also found isomerization of prolinecontaining peptides taking place on different stationary phases in HPLC and Thomas et al [17], Wüthrich et al [18], and Moroder et al [19] in NMR studies.…”
Section: Enalaprilat (1-[n-[(s)-1-carboxy-3-phenylpropyl]-l-alanyl]-mentioning
confidence: 94%
“…Since the publication of Effect of molecular structure and conformational change of proline-containing dipeptides in reversed phase chromatography in 1982, 69 many articles dealing with interconversion profiles obtained by DHPLC of peptidyl-prolin dipeptides have been published, [70][71][72][73][74][75][76][77] but not in all cases the rate constants of cis-trans isomerization were determined. In 1984, Horváth's group 70 published a theoretical article about the determination of rate constants in dynamic reversed-phase chromatography with the help of the Damköhler number.…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…Calixarene-based stationary phases have also proven to be superior in their separation of structurally similar compounds such as o, m, p-substituted aromatics [6 -9], polyaromatic hydrocarbons [4,9,10], cis/trans-isomers of dipeptides [11], and thioxanthenes [5] compared to conventional C 18 phases [4,6,8,11]. However, up to now the retention mechanisms of the calixarene-based stationary phases are not well understood.…”
Section: Introductionmentioning
confidence: 99%